Coping strategies and psychological readiness of students for professional work - V.V. Pichurin (H.S. Skovoroda Kharkov National Pedagogical University, 2015)
Purpose: to find out the current trends regarding the use of students coping strategies. Objectives of the study were to identify the coping strategies that are used by students in the cognitive, emotional and behavioral areas, as well as the identification of adaptive, non-adaptive and adaptive choices regarding their coping behavior. Material: the study involved 600 students (300 - boys, 300 - girls). Age of study participants was 17 - 19 years. Results: the level of students using a number of cognitive, emotional and behavioral strategies has been identified according to the method of E.Heim. The tendencies for the use of students of adaptive, maladaptive and adaptive coping relatively fundamental idea lies behind. Conclusions: the most common coping strategy for students in the cognitive sphere is "self-preservation" in the emotional sphere is "optimism" in the behavioral field is "a distraction." The use of adaptive strategies of students quantify exceedes the use of maladaptive and relatively adaptive (except for behavioral adaptive strategies of boys and girls).